Aleutian Indian and English dictionary [electronic resource] : common words in the dialects of the Aleutian Indian language as spoken by the Oogashik, Egashik, Egegik, Anangashuk and Misremie tribes around Sulima River and neighboring parts of the Alaska peninsula - Lee, Charles A. (Seattle, Wash. : Lowman & Hanford, 1896)
Includes advertising matter. Cover title: Alaska Indian dictionary. "Oogashik, 1896." Electronic reproduction. Mode of access: Internet. 44